Use of Psychodrama in medicine in Brazil: a review of the literature - Rafaela Liberali; Suely Grosseman (Faculdade de Medicina de Botucatu (Unesp), 2015)
Objective To review the literature on experiences of the use of psychodrama in medical education in Brazil.Methods Papers published between 2003 and 2013 were identified in the main databases.Results Seven papers were identified. Role playing and sociodrama were the psychodrama techniques reported. They were used to address aspects of relationships such as emotions and behavior and to improve some communication and clinical skills. Psychodrama provided the students with opportunities for critical reflection, questioning of professional practices and sharing of experiences, and also decreased their anxiety and fear. Role playing was used among students and among teachers undergoing academic development, while sociodrama was only used among students.Conclusions There are still few papers reporting on experiences from the use of psychodrama in Brazilian medical schools.